Screening and Evaluating Reference Genes for Quantitative Real-Time PCR in Striped Jack (Pseudocaranx dentex) - Jiefeng LI; Huan WANG; Busu LI; Xianghui ZENG; Shufang LIU; Zhimeng ZHUANG (Progress in Fishery Sciences, 2023)
Quantitative real-time polymerase chain reaction (qRT-PCR) is one of the most widely used molecular techniques, often implemented to allow for the detection and quantitation of gene expression because of its high sensitivity, specificity, and reproducibility. However, reliable and comparable relative quantitative results using qRT-PCR require the application of appropriate reference genes in order to eliminate non-biological variations caused by initial RNA templates, efficiency of cDNA synthesis, and laboratory procedures. However, previous studies have reported that the stability of many reference genes may vary across species, tissue types, cell lines, developmental stages, and experimental treatments, yielding inaccurate or incorrect gene expression results. Therefore, the selection and validation of stable reference genes for different tissues from a specific species are especially important for obtaining accurate target gene expression results. The striped jack, Pseudocaranx dentex, belonging to the order Perciformes and family Carangidae, is a pelagic migratory fish with high nutritional value. This fish has already received extensive attention in global aquaculture production and is regarded as a candidate species for far-reaching marine aquaculture in China. Given this, there are currently a large number of fairly extensive molecular biology and genetics studies of P. dentex underway, which in turn have increased the demand for quantitative gene expression analysis by qRT-PCR in these animals. However, few studies have evaluated the reference genes for this species. Thus, the objective of this study was to identify suitable reference genes in different tissues of P. dentex, in an effort to provide the necessary tools to support subsequent gene expression pattern analysis.We evaluated nine commonly used reference genes, including beta actin (β-actin), ribosomal protein L13 (RPL13), elongation factor 1 alpha (EF-1α), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), hypoxanthine phosphoribosyl transferase (HPRT), peptidylprolyl isomerase A (PPIA), beta 2-microglobulin (β2M), beta tubulin (TUB), and serine/threonine-protein phosphatase 2A catalytic subunit (PP2A) using qRT-PCR analysis across various P. dentex tissues. These evaluations included the study of their expression stability across ten tissues, including the brain, gill, heart, intestine, kidney, liver, spleen, stomach, slow-twitch muscle, and fast-twitch muscle, from three adult individuals of P. dentex using four independent methods, namely BestKeeper, NormFinder, geNorm, and RefFinder. These results were then validated in the qRT-PCR profiling of the myoblast determination protein 1 (myod1) gene in both muscle (slow-twitch and fast-twitch muscles) and non-muscle tissues (kidney and gills) using the various recommended reference genes or their combinations.Expression analysis showed that RPL13 was the most highly expressed gene in these samples, followed by EF-1α, β2M, β-actin, PPIA, HPRT, TUB, and PP2A, whereas GAPDH was the most weakly expressed across all ten P. dentex tissues. In addition, all nine candidate reference genes exhibited relatively inconsistent variations in Ct value across various tissues, with the BestKeeper stability assay, which uses standard deviation (SD) and coefficient of variation (CV) to score the candidates, suggesting that these genes could be ordered from most stable to least stable as follows: EF-1α > RPL13 > PP2A > PPIA > HPRT > β2M > TUB > GAPDH > β-actin. NormFinder suggested that the ranking was best described as follows: RPL13 > EF-1α > HPRT > TUB > PP2A > PPIA > β2M > GAPDH > β-actin. Evaluations using geNorm, which is based on the idea that the lower the expression stability value (M), the better the stability of gene expression, suggested that the expression stability of these genes is best described as follows: RPL13 = EF-1α > β-actin > GAPDH > PP2A > TUB > PPIA > HPRT > β2M. Finally, RefFinder analysis showed that the comprehensive stability ranking of each gene was RPL13 > EF-1α > PP2A > HPRT > PPIA > TUB > β2M > β-actin > GAPDH. In addition, all of the paired coefficients of variation, Vn/(n+1), reference genes had little effect on the V value. The combination of the two best reference genes is a valid normalization strategy, and the results can be used to correct the expression levels of various target genes. Given this, we can conclude that RPL13 and EF-1α are the two best reference genes for adult tissues. These outcomes were then validated in a myod1 expression assay in the slow-twitch muscle, fast-twitch muscle, kidney, and gills. These experiments revealed no significant differences in relative outcomes when using RPL13, EF-1α, and their combination as reference genes, whereas significant differences were identified when using the three least stable genes β2M, β-actin and GAPDH. This result confirmed that stability evaluation using the four methods was both necessary and effective.Based on our evaluations, we recommend that RPL13, EF-1α, and their combination are the ideal reference gene combinations for all previously evaluated adult tissue types in P. dentex, as verified by four individual algorithms. The results of this study provide the basis for improved standardization of qRT-PCR and transcriptomic evaluations in this species, which in turn should support more accurate evaluation of functional genes and provide technical support for the comprehensive and systematic molecular evaluation of more mature P. dentex samples.